2016
DOI: 10.1186/s40560-016-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of upper airway ultrasound in airway management

Abstract: Upper airway ultrasound is a valuable, non-invasive, simple, and portable point of care ultrasound (POCUS) for evaluation of airway management even in anatomy distorted by pathology or trauma. Ultrasound enables us to identify important sonoanatomy of the upper airway such as thyroid cartilage, epiglottis, cricoid cartilage, cricothyroid membrane, tracheal cartilages, and esophagus. Understanding this applied sonoanatomy facilitates clinician to use ultrasound in assessment of airway anatomy for difficult intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 50 publications
0
88
0
3
Order By: Relevance
“…Various structures such as base of the tongue, epiglottis, hyoid bone, vocal cords, thyroid cartilage, cricoid cartilage, cricothyroid membrane, and oesophagus can be seen on the sono-anatomy. Developing this skill will help the anaesthetist to assess the airway for difficult intubation, confirming the placement of endotracheal tube into the trachea, predicting the appropriate size of laryngeal mask airway and endotracheal tube, identifying oesophageal intubation, and identifying the cricothyroid membrane for front of neck access [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various structures such as base of the tongue, epiglottis, hyoid bone, vocal cords, thyroid cartilage, cricoid cartilage, cricothyroid membrane, and oesophagus can be seen on the sono-anatomy. Developing this skill will help the anaesthetist to assess the airway for difficult intubation, confirming the placement of endotracheal tube into the trachea, predicting the appropriate size of laryngeal mask airway and endotracheal tube, identifying oesophageal intubation, and identifying the cricothyroid membrane for front of neck access [1].…”
Section: Discussionmentioning
confidence: 99%
“…Upper airway ultrasound is a skill that is yet to become universal amongst the anaesthesia community. Various studies have been performed and have shown that upper airway ultrasound is beneficial in predicting difficult laryngoscopy, predicting the size of endotracheal tube, identifying correct endotracheal and laryngeal mask airway placement, identifying the cricothyroid membrane, prediction of post-extubation stridor and evaluation of the epiglottis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound machines have already been recognized as a highly effective tool for assessing the overall anatomy of the neck. More recently, as its technology becomes more refined, its use has been explored and expanded upon to allow for more effective assessment and evaluation of the airway . Point‐of‐care ultrasound is in fact becoming an important tool in pediatric airway diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…With great interest, I read the article by Osman et al, entitled “Role of upper airway ultrasound (US) in airway management” [1]. The authors reviewed thoroughly for the various US applications for the upper airway, including prediction of endotracheal tube (ETT) size, difficult laryngoscopy, airway device placement and depth, percutaneous cricothyroidotomy, prediction of post-extubation stridor, and evaluation of the epiglottis.…”
mentioning
confidence: 99%
“…The esophagus is located at the posterior area of the left lobe of the thyroid gland [1]. Tracheal intubation is identified if only one A–M interface is present with one comet-tail artifact.…”
mentioning
confidence: 99%